The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1158/1541-7786.mcr-12-0455
|View full text |Cite
|
Sign up to set email alerts
|

The ATPase Activity of Reptin Is Required for Its Effects on Tumor Cell Growth and Viability in Hepatocellular Carcinoma

Abstract: Reptin is overexpressed in most human hepatocellular carcinomas. Reptin is involved in chromatin remodeling, transcription regulation, or supramolecular complexes assembly. Its silencing leads to growth arrest and apoptosis in cultured hepatocellular carcinoma cells and stops hepatocellular carcinoma progression in xenografts. Reptin has an ATPase activity linked to Walker A and B domains. It is unclear whether every Reptin function depends on its ATPase activity. Here, we expressed Walker B ATPase-dead mutant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 27 publications
(51 reference statements)
0
32
0
Order By: Relevance
“…For many ATPases such as AAA þ ATPases, Hsp90, and Dnd, the ATPase activity is vital for their physiologic functions (27,41,42). To identify whether an intact endostatin ATPase activity is required for its antiangiogenic effects, we assessed the inhibitory effects of endostatin and its mutants on endothelial cell proliferation, migration, tube formation, and adhesion.…”
Section: The Atpase Activity Of Endostatin Mediates Its Effects On Enmentioning
confidence: 99%
“…For many ATPases such as AAA þ ATPases, Hsp90, and Dnd, the ATPase activity is vital for their physiologic functions (27,41,42). To identify whether an intact endostatin ATPase activity is required for its antiangiogenic effects, we assessed the inhibitory effects of endostatin and its mutants on endothelial cell proliferation, migration, tube formation, and adhesion.…”
Section: The Atpase Activity Of Endostatin Mediates Its Effects On Enmentioning
confidence: 99%
“…Rosenbaum’s group now shows that the ATPase activity of Reptin is required for sustaining tumor cell growth, suggesting that Reptin could be a viable drug target for cancer therapy (37). In collaboration with Michel Laguerre’s group (Institut Européen de Chimie et de Biologie, Pessac, France), Patrick Lestienne, from the Rosenbaum group, presented small molecule inhibitors of Pontin’s ATPase activity identified through in silico modeling and in vitro testing (38).…”
Section: Pathophysiology and Therapeutic Targetingmentioning
confidence: 99%
“…For example, ATPase activities of both proteins are required for regulation of heart growth in zebrafish embryos [33] and c‐Myc‐induced cell transformation [20]. It is also been shown that the ATPase activity of Reptin is required for tumor cell growth in HCC [26]. On the other hand, the ATPase activity is dispensable for some of Reptin functions such as repression of the influenza A virus polymerase [34] and of the transcriptional activity of ATF2 [23].…”
Section: Discussionmentioning
confidence: 99%